Using Radiocarbon to Assess the Abundance, Distribution, and Nature of Labile Organic Carbon in Marine Sediments - DeMaster, D. J.; Taylor, R. S.; Smith, C. R.; Isla, E.; Thomas, C. J. (Global Biogeochemical Cycles, 2021)
Positive C-14 gradients have recently been observed within the surface mixed layer of several continental-margin sediments. The best explanation for these positive C-14 gradients is the occurrence and rapid degradation of labile organic carbon (LOC) in the upper 5-10 cm of the seabed. Based on a two-component model for sedimentary organic matter (i.e., a planktonic labile component and an older refractory component), bulk (14)Corg data were used to determine the abundances of LOC within the surface mixed layers of three cores from the West Antarctic Peninsula (WAP) shelf and one core from San Clemente Basin (California Borderland). LOC contents in surface samples from the four stations varied from 0.5 to 1.1 mg/cm(3), comprising 20% (San Clemente Basin) to 80% (WAP, Sta. G) of the total organic carbon. By incorporating a steady state diagenetic model and particle-mixing bioturbation coefficients, the LOC profiles were used to determine LOC turnover times (LOC tau) and LOC e-folding depths. The LOC tau values for the West Antarctic Peninsula sediments varied from 0.09 to 0.59 years, whereas the LOC tau value from the San Clemente Basin core was 63 years. The LOC e-folding depths for the WAP stations varied from 0.8 to 3.4 cm, in contrast to the LOC e-folding depth in San Clemente Basin, which was 4.0 cm. LOC characteristics from the four cores examined in this study were compared to LOC data in the literature as a means of substantiating the overall C-14(org)-based approach and justifying model assumptions.